Estimating the infection severity and infection percentage by aphids on eggplant varieties - Aljuboory, Ahmed Bakir (Journal of Aridland Agriculture, 2023)
Finding a new source of resistance is important to reduce the use of synthetic pesticides, which can meet the global need of suppressing pollution. In this study, the resistance of eight eggplant cultivars to Aphis gossypii was evaluated. Results of the current study highlighted that the cultivar Long-Green has a very strong resistance after 14 days post infestation whereas Pearl-Round and White-Casper cultivars were susceptible. The rest of the tested cultivars (Green-oblong, Purple-panter, Paris, Ashbilia, and Barcelona) had mild resistance. Also, the study found significant differences between the infested and non-infested plants among the tested cultivars in the plant’s height, fresh-, and dry-weight. The susceptible cultivars lost about 30% of their height, fresh- and dry-weight after the infestation compared with the cultivars that had mild resistance. Pearl-Round and White-Casper showed a very strong susceptibility among the evaluated cultivars which may be used as an element in the pest control program against A. gossypii.